Formal synthesis of dibenzotetrathiafulvalene (DBTTF), through practical electrochemical preparation of benzo[d]-1,3-dithiole-2-one (BDTO) - Terán-Alcocer, Álvaro V.; Cifuentes-Ajuchan, Fernanda M. J.; López-Mayorga, Byron J.; Frontana-Uribe, Bernardo A. (Frontiers in Chemistry, 2025)
This study focuses on developing an electrochemical reaction to produce benzo[d]-1,3-dithiole-2-one (BDTO). This compound serves as a direct precursor for dibenzotetrathiafulvalenes (DBTTF), an important member of the charge transfer complex family. BDTO is synthesized in three steps (16%) starting from aniline. The key reaction is an anodically driven intramolecular cyclization (35%), involving a thiyl radical-cation intermediate formed from the oxidation of the S-aryl-O-ethyldithiocarbonate derivative. This derivative is obtained in good yields from its respective aromatic diazonium salt. This approach eliminates the need for advanced, costly intermediates and avoids long, complex synthetic routes previously used to produce BDTO, utilizing safer and cheaper reagents. This opens the door to generating DBTTF derivatives quickly.